Pesta Rakyat Pada Malam Hari Banyak Menimbulkan Kemudharatan - Nurjulia Darselo; Ema Fathimah (Journal of Sharia and Legal Science, 2023)
People's parties are defined as activities held to commemorate important things throughout human life, either individually or in groups related to customs, culture, traditions and religion, which are held for specific purposes and involve the community environment which are held at certain times. The problem of this research is because the people of Maur Lama Village, Rupit District, North Musi Rawas Regency held a people's party according to or not with the Regional Regulation of North Musi Rawas Regency No. 17 of 2019 concerning the People's Party. In this context, the problem to be discussed is formulated as a ban on Regional Regulation of North Musi Rawas Regency No. 17 of 2019 concerning People's Parties as well as a review of Islamic criminal law regarding the prohibition of people's parties which are carried out at night in Maur Lama Village, Rupit District, North Musi Rawas Regency. This research includes empirical juridical, while the specification of this research is descriptive qualitative. The sampling used in this research is purposive sampling. This research concluded deductively. The conclusion of this study is that the prohibition of people's parties at night in Maur Lama Village, Rupit District, North Musi Rawas Regency is in accordance with the enactment of North Musi Rawas District Regulation No. 17 of 2019 concerning the People's Party. Which for violators will be subject to punishment in Article 15 Regional Regulation of North Musi Rawas Regency No. 17 of 2019 concerning the People's Party which contains "convicted with a maximum imprisonment of 3 (three) months and/or a maximum fine of Rp. 50,000,000.- (fifty million rupiah)”. So that the existence of these provisions makes citizens think twice about violating these rules. In Islamic criminal law, night party sanctions are categorized as jarimah ta'zir because people's parties in Islamic law have not been legally stipulated by Syara'. As for the night party activities, it causes more harm.